Biodiversity Change in Cultural Landscapes—The Rural Hotspot Hypothesis - Carsten Neumann; Robert Behling; Gabriele Weiss (Ecology and Evolution)
ABSTRACT A dramatic decrease of biodiversity is currently questioning human‐environment interactions that have shaped ecosystems over thousands of years. In old cultural landscapes of Central and East European (CEE) countries, a vast species decline has been reported for various taxa although intensive land cultivation has been reduced in favor of agroecological transformation, nature conservation and sustainable land management in the past 30 years. Thus, in the recent history, agricultural intensification cannot solely be discussed as the major driver controlling biodiversity. In cultural landscapes, we state that drivers and pressures mainly emerge from the backyards of rural settlements that act as interconnected rural hotspots and therefore form an ecological metapopulation in which small‐scale backyard habitats are capable of preserving and exchanging species pools of the historical cultural landscape. We further argue that shifting sociocultural norms significantly affecting the survival of source populations in rural hotspots and drastically limit their dispersal pathways, which triggers the degradation of the rural metapopulation in recent times. Pressures of cultivation shift, landscape decoupling, structural homogenization, and use of technology and agrochemicals are identified as backyard ecological drivers negatively affecting biodiversity preservation, particularly in the surrounding rural landscape. Spatiotemporal dimensions of backyard pressures involving material fluxes, species exchange and retention, alternation of site conditions, and local genetic adaptation are delineated for different backyard features, including building structures, gardens, lawns, and paved grounds. Finally, we propose a future research agenda to quantify effects and trends of rural hotspots and followed patterns of altered species dynamics. We give an example on the use of satellite time series to remotely map rural backyard habitats and reveal significant spatiotemporal trends induced by small‐scale human behavior that may lead to a new socioecological perception and stimulate actions to shape ecological dynamics emerging from the backyards of human settlements.